1990
DOI: 10.1111/j.1440-1827.1990.tb01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Carcinomata Associated with Anomalous Arrangement of the Biliary and Pancreatic Duct System

Abstract: Two rare cases of multiple neoplasms occurring in association with anomalous arrangement of the pancreatobiliary duct system (PBD) are reported. Ultrasonography, computed tomography and endoscopic retrograde cholangiopancreatography revealed cholecystic tumor in the first case, and multiple choledochocholecystic tumors in the second case. In the first case, pancreatic tumor was discovered two years after cholecystectomy. In the second case, a pancreatic tumor was discovered incidentally in the removed pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, the preferential occurrence of mucinous cystic tumours in the distal rather than the proximal pancreas, the high preponderance of female patients as well as the distinctive gross morphology clearly separate these tumours from IPMT (5,37,44,52). Considering the histological and histochemical similarities of many IPMT (especially the malignant ones) with well differentiated papillary-villous colorectal, ampullary and biliary tract tumours (31), and the reported cases with simultaneous involvement of biliary tract, ampulla and pancreas by papillary tumours (21,24,25), it seems possible that some relationship may exist between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the preferential occurrence of mucinous cystic tumours in the distal rather than the proximal pancreas, the high preponderance of female patients as well as the distinctive gross morphology clearly separate these tumours from IPMT (5,37,44,52). Considering the histological and histochemical similarities of many IPMT (especially the malignant ones) with well differentiated papillary-villous colorectal, ampullary and biliary tract tumours (31), and the reported cases with simultaneous involvement of biliary tract, ampulla and pancreas by papillary tumours (21,24,25), it seems possible that some relationship may exist between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…There have been 27 reported cases (including ours) of cancer of the pancreas in patients who had pancreaticobiliary maljunction. Double cancer of the biliary tree and pancreas in patients with pancreaticobiliary maljunction has been reported in seven patients including ours (two cases were triple cancer of the gallbladder, the bile duct, and the pancreas) . (Table 1).…”
Section: Discussionmentioning
confidence: 66%
“…However, the relationship between pancreatic cancer and PBM remains controversial and unclear. In addition, cases of double cancer of the biliary system and the pancreas is extremely rare in patients with PBM (8,(10)(11)(12), despite occasional reports of multiple cancers of the biliary system in patients with PBM (3)(4)(5). The present case suggested that careful attention should be paid to the whole pancreaticobiliary system with regard to carcinogenesis, however, further case studies are needed.…”
Section: Discussionmentioning
confidence: 67%
“…The definitive distinction between multicentric primary cancers and gallbladder cancer metastases is difficult. Although biliary cancer in patients with PBM is occasionally encountered, pancreatic cancers in patients with PBM are rare (8)(9)(10)(11)(12). Funabiki et al (13) reported that the incidence of pancreatic cancer is higher in patients with PBM than in patients without PBM.…”
Section: Discussionmentioning
confidence: 99%